Active fraction (HS7) from Taiwanofungus camphoratus inhibits AKT-mTOR, ERK and STAT3 pathways and induces CDK inhibitors in CL1-0 human lung cancer cells - I-Chun Lai; Gi-Ming Lai; Jyh-Ming Chow; Hsin-Lun Lee; Chuan-Feng Yeh; Chi-Han Li; Jiann-Long Yan; Shuang-En Chuang; Jacqueline Whang-Peng; Kuan-Jen Bai; Chih-Jung Yao (BMC, 2017)
Abstract Background The non-small cell lung cancer (NSCLC) is the leading cause of cancer death worldwide. In NSCLC, the oncogenic AKT-mTOR, ERK and STAT3 pathways are commonly dysregulated and have emerged as attractive targets for therapeutic developments. In a relatively limited subset of NSCLC, these pathways driven by mutant EGFR can be treated by the tyrosine kinase inhibitors (TKIs)-mediated targeted therapy. However, for the most NSCLC, more novel targeted agents are imperatively needed. Therefore, we investigated the inhibitory effects of the active fraction HS7 from Taiwanofungus camphoratus, a unique medicinal fungus in Taiwan, on these pathways in CL1-0 EGFR wild-type human NSCLC cells. Methods The active fraction HS7 was prepared by n-hexane extraction of T. camphoratus followed by silica gel chromatography. Its effects on the cell viabilities were determined by sulforhodamine B colorimetric assay. Flow cytometry was used to analyze cell-cycle regulation and apoptosis induction. The changes in cellular protein levels were examined by Western blot. Results The active fraction HS7 vigorously inhibits AKT-mTOR, ERK and STAT3 signaling pathways in CL1-0 cells. At dose of 25 μg/mL, these signaling pathways were almost completely inhibited by HS7, accompanied with induction of cyclin-dependent kinase inhibitors such as p15, p21 and p27. Accordingly, the AKT-mTOR downstream targets p-p70S6K and HIF-1α were also suppressed as well. At this dose, the cell proliferation was profoundly suppressed to 23.4% of control and apoptosis induction was observed. Conclusions The active fraction HS7 from n-hexane extract of T. camphoratus exerts multi-targeting activity on the suppression of AKT-mTOR, ERK and STAT3 pathways and induction of p15, p21 and p27 in EGFR wild-type NSCLC cells. This multi-targeting activity of HS7 suggests its potential as an alternative medicine for the treatment of EGFR TKIs resistant NSCLC.